Radiation oncology in the era of precision medicine - Baumann, Michael; Krause, Mechthild; Overgaard, Jens; Debus, Jürgen; Bentzen, Søren M.; Daartz, Juliane; Richter, Christian; Zips, Daniel; Bortfeld, Thomas (Nature reviews. Cancer, 2016)
This Review discusses technological and biologically based advances in radiotherapy. The authors envisage that these two major strategies will act synergistically to further widen the therapeutic window of radiation oncology in the era of precision medicine.